Assessing the impact of forest structure disturbances on the arboreal movement and energetics of orangutans—An agent-based modeling approach - Widyastuti, Kirana; Reuillon, Romain; Chapron, Paul; Abdussalam, Wildan; Nasir, Darmae; Harrison, Mark E.; Morrogh-Bernard, Helen; Imron, Muhammad Ali; Berger, Uta (Frontiers in Ecology and Evolution, 2022)
Agent-based models have been widely employed to assess the impact of disturbances or conservation management on animal habitat use, population development and viability. However, the direct impacts of canopy disturbance on the arboreal movement of individual primates have been less studied. Orangutans are arboreal primate that commonly encounters habitat quality deterioration due to disturbances such as forest fires. Forest disturbance may therefore create a complex stress scenario threatening orangutan populations. Due to forest disturbances, orangutans may adapt to employ more terrestrial, as opposed to arboreal, movements. In turn, this may lead to changes in daily activity patterns and available energy budget, potentially decreasing orangutan’s fitness. We developed the agent-based simulation model BORNEO (arBOReal aNimal movEment mOdel), which explicitly describes both orangutans’ arboreal and terrestrial movement in a forest habitat, depending on distances between trees and canopy structures. We tested the model using forest inventory data obtained in Sebangau National Park, Central Kalimantan, Indonesia. This allowed us to construct virtual forests with real characteristics including tree connectivity. We applied a computationally intensive evolutionary algorithm and evaluated the simulation results against observed behavioural patterns of orangutans. Both the simulated variability and proportion of activity budgets confirmed the suitability of the model for its purpose. We used the calibrated model to compare the activity patterns and energy budgets of orangutans in both natural and disturbed forests. The results confirm field observations that orangutans in disturbed forest are more likely to experience deficit energy balance due to travelling in detriment of feeding time. Such imbalance is more pronounced in males than in females. The finding of a threshold of forest disturbances which affects a significant change in activity and energy budgets suggests potential threats to the orangutan population. Our study introduces the first agent-based model describing the arboreal movement of primates that can serve as a tool to investigate the direct impact of forest changes and disturbances on the behaviour of species such as orangutans. Moreover, it demonstrates the suitability of high-performance computing to optimise the calibration of complex agent-based models describing animal behaviour at a fine spatio-temporal scale (1-meter and 1-second granularity).